Bookings through the hotel's website: Factors influencing perceived value and customer loyalty, mediated by satisfaction - Garcia,Gisele Magrini (2025)
Abstract Technological progress and internet popularization enabled the emergence of new distribution channels in tourism, including direct sales by the hotels’ websites. The interaction with the hotels' websites strengthens social interactivity, creating personalized and unique experiences, and improving value to customers. The study assesses whether/how the appearance and usability of the website, and the need for interaction, influence guests’ perceived value, satisfaction, and loyalty, in the hotel industry. The data was scrutinized by Confirmatory Factor Analysis, to assess reliability and validity, and by Structural Equation Modelling, both using the WarpPLS algorithm. The result confirmed the influence of the need for interaction and the appearance and usability of the website on perceived value, and the last one on satisfaction, and loyalty, thus corroborating the findings of previous research; the result also confirmed the mediating effect of satisfaction on guests loyalty, which is also in line with previous results. The study is limited in that it looked at the experience on hotel websites in general, rather than specific categories. For future studies, the authors suggest comparing the model across units of different categories, or hotels specialized in specific segments.